32.7k views
4 votes
X + 3y + 2z = 7

2x- y+z=9
-z+ 4y + 5z = 14

The answers are 2,-1,4 but I need help with showing the work plzzzz!!!

X + 3y + 2z = 7 2x- y+z=9 -z+ 4y + 5z = 14 The answers are 2,-1,4 but I need help-example-1
User Drdilyor
by
5.2k points

1 Answer

4 votes

Explanation:

x + 3y + 2z = 7

2x − y + z = 9

-x + 4y + 5z = 14

First add the first and third equations to eliminate x.

7y + 7z = 21

Simplify:

y + z = 3

Solve for y:

y = 3 − z

Substitute into the first two equations:

x + 3(3 − z) + 2z = 7

2x − (3 − z) + z = 9

Simplify:

x + 9 − 3z + 2z = 7 → x − z = -2

2x − 3 + z + z = 9 → 2x + 2z = 12 → x + z = 6

Add the equations to eliminate z.

2x = 4

x = 2

Therefore, z = 4 and y = -1.

User Seth Holladay
by
5.7k points